Penguatan Kewirausahaan Komunitas Berbasis UMKM di Desa Kota Pari Deli Serdang - Indrawan, Muhammad Isa; Fatmawati, Irma; Rahayu, Sri (Jurnal Semarak Mengabdi, 2025)
This community service activity aims to strengthen the entrepreneurial capacity of MSME-based communities in Kota Pari Village, Deli Serdang Regency. The main problems faced by partners are low managerial skills, limited marketing access, and the suboptimal innovation of local products with economic potential. Through an integrated training approach and intensive mentoring, this activity covers aspects of developing an entrepreneurial mindset, product innovation techniques, digital marketing strategies, and simple financial literacy. The implementation method is carried out through initial observations, group discussions, interactive training, and evaluation of activity results. The results of the activity show an increase in entrepreneurial knowledge and skills among participants, as well as the emergence of several follow-up plans for sustainable local business development. This activity is expected to be the first step in establishing an independent and competitive village entrepreneurial ecosystem amidst the dynamics of the digital economy.